Modification of Human Behavior due to Coronavirus Outbreak: A Brief Study on Current Scenario (Asian Journal of Pharmaceutics (AJP), 2021)
Purpose: The objectives of present study were to evaluate the properties of a behavior modification of peoplein India associated with coronavirus outbreak. The behavior modification is measure of coronavirus relatedpsychopathology, which was validated through a large sample study on adults who reported significant changein behavior due to watching and reading about coronavirus pandemic. Methods: Door to door and online surveyconducted in Morena and Gwalior District, Madhya Pradesh, India, for collection of data of 1050 adults’.The partakers were contacted individually, through online and complete information were taken out through aquestionnaire of different parameters. Because the study focused on the effect of thinking and/or watching aboutcoronavirus disease 2019 (COVID-19) on physical activity of body, behavior, mental stress, anxiety, faith inGod, and appetite. Results: A total of 16 symptoms of behavior modification due to coronavirus outbreak werestatistically defined through a principal component analysis with Varimax rotation. The results were confirmed bya two-component structure and the total variance explained 55.23% for first component accounting. The six primeloadings on the first component were selected for the behavior changes because these loadings well exceededthe criteria for psychometrically prime items. Especially, communalities extraction coefficients (CEC) rangedfrom 0.717 to 0.853, coefficients of structure/pattern ranged from 0.71 to 0.90, and cross-loadings ranged from0.17 to 0.22. These symptoms were used for the determination of different parameters such as decreased physicalactivity, psychological disturbances, mental stress, anxiety, faith in God, and appetite before arising COVID-19infection and were highly reliable (α = 0.83) as a cluster. Conclusion: For the coronavirus outbreak, models willbe required for control the negative behavior modification of peoples so that they can use their skill for positiveoutcomes. The clear cut updated policy of should be implemented to reduce these types of modifications. Theprime symptoms of behavior modification were validated and stabilized through statistical tools such as CEC,coefficients of structure/pattern, and analysis of variance. Hence, we can say that if opinions of some expertsare correct, then world’s most of population need special care to avoid behavior modification due to coronavirusoutbreak.